Stiffening hydrogels for investigating the dynamics of hepatic stellate cell mechanotransduction during myofibroblast activation - Caliari, Steven R. (Sci Rep, 2016)
Tissue fibrosis contributes to nearly half of all deaths in the developed world and is characterized by progressive matrix stiffening. Despite this, nearly all in vitro disease models are mechanically static. Here, we used visible light-mediated stiffening hydrogels to investigate cell mechanotransduction in a disease-relevant system. Primary hepatic stellate cell-seeded hydrogels stiffened in situ at later time points (following a recovery phase post-isolation) displayed accelerated signaling kinetics of both early (Yes-associated protein/Transcriptional coactivator with PDZ-binding motif, YAP/TAZ) and late (alpha-smooth muscle actin, α-SMA) markers of myofibroblast differentiation, resulting in a time course similar to observed in vivo activation dynamics. We further validated this system by showing that α-SMA inhibition following substrate stiffening resulted in attenuated stellate cell activation, with reduced YAP/TAZ nuclear shuttling and traction force generation. Together, these data suggest that stiffening hydrogels may be more faithful models for studying myofibroblast activation than static substrates and could inform the development of disease therapeutics.